From network to class? Towards a more complex conception of connection and sociability - France Bourgouin (Danish Institute for International Studies (DIIS), 2009)
The notion of networks is frequently used by social science scholars in order to explain various forms of social and economic linkages. In this Working Paper, I question why it is that we have replaced older notions of sociality such as culture, community, or group with network, and what the analytical gains are if any. Building upon recent ethnographic fieldwork conducted with foreign African businessmen and women employed in Johannesburg's tertiary sector multinational corporate, I argue that the network approach is too narrow a way for conceiving the linkages and connections between individuals; the processes and institutional channels that connect individuals may not be so apparent and 'mappable' but rather much more diffuse and context-based.
Keywords: 330; Soziales Netzwerk; Soziale Beziehungen; Sozialwissenschaft; Theorie; Südafrika